PENAMAAN OBJEK WISATA ALAM DAN BUDAYA KABUPATEN BENGKAYANG: KAJIAN ANTROPOLINGUISTIK - Rosdiana, Eva; Sulissusiawan, Ahadi; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the background of naming, the meaning of naming, and the cultural values contained in the names of natural and cultural attractions of Bengkayang Regency. The method used in this study is a descriptive method with a qualitative form. The source of data in this study is the indigenous people of Bengkayang Regency who know the background of naming natural and cultural attractions. Data collection techniques in this study used direct techniques, namely observation of participation and periods to the field, interview, note taking, recording, and documentation. This research resulted in 70 names of natural and cultural attractions with details of 8 naming based on anomatic, 3 based on sound imitation, 2 based on parts, 13 based on distinctive properties, 12 based on inventors and makers, 9 based on place of origin, 14 based on materials, 6 based on similarity, and 3 based on new naming. The meanings of names found in this study are 8 meanings of futurative names, 43 meanings of situational names, and 19 meanings of memory names. The cultural values found in this study are 1 welfare value, 5 hard work values, 1 health value, 17 cultural preservation and creativity values, 30 environmental care values, 2 peace values, 2 harmony and conflict resolution values, 2 solidarity values, 1 commitment value, 6 positive thought values, and 3 gratitude values.